Triterpenoid profiles of the leaves of wild and domesticated grapevines - Burdziej, Aleksandra; Pączkowski, Cezary; Destrac-Irvine, Agnès; Richard, Tristan; Cluzet, Stéphanie; Szakiel, Anna (Phytochemistry letters, 2019)
The composition of steroids and triterpenoids in the leaves of eight grapevine species was analyzed in order to assess phenotypic differences. Four wild species (Vitis aestivalis Michx., Vitis labrusca L., Vitis riparia Michx., and Vitis vinifera subsp. sylvestris (Gmelin) Hegi) and four domesticated (Vitis vinifera cultivars: Cabernet Sauvignon, Gamay, Marselan, and Merlot) were studied. Although the main profiles of steroids and triterpenoids were similar in all analyzed extracts, remarkable quantitative differences in the content of these compounds in Vitis spp. leaves were demonstrated by GC-MS/FID analysis. The analyzed Vitis plants differed in the level of phytosterols, i.e. cholesterol (1), campesterol (2), stigmasterol (3), clionasterol (4) (exclusively in V. vinifera subsp. sylvestris (Gmelin) Hegi), sitosterol (5), and their amount was generally higher in wild grapevines. The predominance of pentacyclic triterpenoids of ursane-, oleanane-, lupane- and friedooleanane (taraxerane)-type skeletons depended on the studied cultivar/variety. Taraxerol (7) may be considered as a biomarker compound of V. vinifera leaves. The obtained data supplement information about biochemical diversity of Vitis genus and despite small qualitative differences allow species discrimination considering phylogenetic relationships confirmed by HCPC analysis. Differences between wild and cultivated grapevines in steroid and triterpenoid profiles may be connected to the domestication process.